2012
DOI: 10.1007/s00267-012-9880-z
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Re-Introduction of Endangered Plant Species: The Case of German False Tamarisk in Pre-Alpine Rivers

Abstract: The scope of re-introduction as a measure for plant species protection is increasing, but as long as no standardized methods are available, species-specific assessments are necessary to determine whether seeds, adult plants or plant fragments should be used. The endangered German False Tamarisk (Myricaria germanica), which occurs on gravel bars along pre-alpine rivers, is difficult to grow from seeds. Thus, propagation of stem cuttings was investigated as an alternative method. Experiments were conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…In the ex situ experiment, the resprouting rate after taking cuttings was consistent with other published results for Mg [95 and 70 %, respectively, in a laboratory experiment for Schiechtl (1973) and Koch and Kollmann (2012)] and for Sp [100 % according to Graf et al (2003); (Venti et al 2003); Zuffi (1989)]. No comparative data were found for Tg, but most of the authors state that cuttings have very good resprouting capacity (Carleton 1914;Gary and Horton 1965;Everitt 1980;Hartmann et al 1996;Walker et al 2006).…”
Section: What Have We Learned?supporting
confidence: 90%
See 2 more Smart Citations
“…In the ex situ experiment, the resprouting rate after taking cuttings was consistent with other published results for Mg [95 and 70 %, respectively, in a laboratory experiment for Schiechtl (1973) and Koch and Kollmann (2012)] and for Sp [100 % according to Graf et al (2003); (Venti et al 2003); Zuffi (1989)]. No comparative data were found for Tg, but most of the authors state that cuttings have very good resprouting capacity (Carleton 1914;Gary and Horton 1965;Everitt 1980;Hartmann et al 1996;Walker et al 2006).…”
Section: What Have We Learned?supporting
confidence: 90%
“…4) confirmed a strong belowground biomass production and an important drought acclimatization. In a recent experiment on Mg cuttings with different treatments in terms of cutting length, planting depth, and water levels, the authors found that an overall SRR of 10 after 4 months is found (Koch and Kollmann 2012), which is consistent with results. They do not find any significant difference in SRR between two tested water levels, even if they find, as in our study, a small decrease of the SRR for the lowest water level.…”
Section: What Have We Learned?supporting
confidence: 75%
See 1 more Smart Citation
“…The problem of propagule supply can be efficiently solved by the quasi in situ living collections as explained below, and the crucial knowledge about species propagation, although still very limited, is steadily accumulating for rare and endangered species (e.g. Iturriaga et al., 1994, Sakai et al., 2002, Danthu et al., 2008, De Motta, 2010, Herranz et al., 2010, Kay et al., 2011, Ratnamhin et al., 2011, Koch and Kollmann, 2012, Castellanos-Castro and Bonfil, 2013, Gratzfeld et al., 2015, Lu et al., 2016). Once the necessary knowledge is acquired and protocols are available, comparable to those for common species, the cost per seedling will make restoration practitioners more likely to incorporate rare and threatened species into their plans (Rodrigues et al., 2011), because availability of seedlings rather than the cost of a seedling per added species is an obstacle to planting high-diversity species pools (Aronson et al., 2011).…”
Section: Conservation-oriented Restorationmentioning
confidence: 99%